The effect of tlr4 agonist (crx-527) on il-10 production in mice immunized with bcg-msp-1c - Zaman, Tabassum Irin (Universiti Sains Malaysia, 2025)
Malaria, caused by the Plasmodium parasite, continues to be a significant global health burden, particularly in regions with limited access to healthcare. Current malaria vaccines face challenges of suboptimal efficacy and logistical barriers for widespread implementation. One promising antigen for malaria vaccine development is the C-terminal region of merozoite surface protein 1 (MSP-1C), a conserved fragment of MSP-1, the major surface protein of Plasmodium merozoites, which is essential for red blood cell invasion and evasion of host immune responses. This study evaluates the impact of the Toll-like receptor 4 (TLR4) agonist CRX-527 on IL-10 production in mice immunized with the BCG-MSP-1C vaccine, developed in our laboratory by cloning the MSP-1C antigen with the Bacillus Calmette–Guérin (BCG) vaccine, which is primarily used for tuberculosis (TB) prevention. Treatment groups included PBS-T80, LPS, BCG, and BCG-MSP-1C. The results revealed a significant enhancement of IL-10 production across all groups in both liver and lymph node supernatant samples in the presence of CRX-527. Among these, the BCG-MSP-1C group exhibited the highest IL-10 levels, followed by the BCG, LPS, and PBS-T80 groups. IL-10, an anti-inflammatory cytokine, plays a pivotal role in regulating the immune response, ensuring controlled infection management while minimizing tissue damage. These findings highlight CRX-527’s potential as an effective immune-modulatory adjuvant for malaria vaccine strategies. The incorporation of CRX-527 with the BCG-MSP-1C vaccine offers a dual immunization approach, enabling protection against both malaria and tuberculosis with a single immunization. This strategy could significantly reduce the burden of multiple vaccine doses and improve immunization coverage in resource-limited settings. The study underscores the potential of CRX-527 to enhance vaccine efficacy and promote long-term immunity, supporting its role in advancing cost-effective, dual-purpose vaccine solutions for endemic regions